A expansão urbana e sobreposição territorial na cidade de Cascavel, Paraná - Nogueira , Caroline Scheffer (2021)
Urban Planning is part of the territorial structuring of cities, through Municipal Master Plans, which provide guidelines and norms for the use and occupation of the land, through indexes and rates established in accordance with the zoning. These Master Plans are the result of the Cities Statute, and serve to stipulate short, medium and long-term actions for the entire municipal territory. So, from observations on the growth and territorial expansion of cities dedicated to agribusiness, this study was proposed. It is noted that as territorial expansion occurs, urban areas enter rural areas, and in this space, there is conflict of uses, that is, it does not differentiate where one begins or the other ends. Where this miscegenation between rural and urban occurs, it is customary to call transition areas, which in most cases do not have clearly established rules in the Municipal Master Plans. The concern of this thesis refers to the antagonism of activities developed, more precisely the use of space in these areas, since when urbanized, they are divided into lots and inhabited, but when rural, they are destined for agricultural cultivation. And precisely with regard to these properties dedicated to agribusiness, attention must be redoubled, as pesticides are applied to these plantations. It is known that the use of pesticides poses risks of intoxication, and even studies point to diseases linked to exposure to pesticides, either directly or indirectly. Therefore, the Municipality of Cascavel was chosen as the stage for studies, as it is a region of high agricultural potential, with an economy geared towards agribusiness. For this, an area located in the western region of the city was established, where urban expansion is evident, and there are also areas dedicated to agribusiness, in many cases, the rural and urban are limited only by a boundary of lots, a wall , and while a family lives on one side, an agricultural machine sprays pesticides on the other. Based on this situation of conflicts of land use and occupation, where rural and urban are confused, an urbanistic tool was proposed to assist the Master Plans of municipalities dedicated to agribusiness. This tool is the result of the thesis, as it is noted that the transition areas do not receive due attention, it is necessary to differentiate the uses, to ensure people's quality of life, that is, to ensure growth with development, especially in terms of it's about sustainability. The much talked about sustainable development must be part of both the urban and the rural, it is believed that planning a city is not just looking at the urban, but looking at the whole, this planning must be territorial.